INVESTIGASI PENGARUH KONDISI LALU LINTAS DAN ASPEK METEOROLOGI TERHADAP KONSENTRASI PENCEMAR SO2 DI KOTA SEMARANG - Istirokhatun, Titik; Agustini, Ita Tetriana; Sudarno, Sudarno (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2016)
The  presence  of  air  pollution  in  ambient  air  is  closely  related  to  the incidence  of  adverse reactions affecting human health. One of harmful pollutants and potentially major cause health problems is sulfur dioxide (SO 2 ). The number of vehicles that are passing and queuing on the crossroads  because  of  traffic light can  affect  the  concentration  of  SO 2 .  Besides,  in  these locations  there  are a lot of road users  which  are  potentially  exposed  by  contaminants, so information about the concentration of SO 2  is important to know. This study aimed to investigate the  impact  of  meteorological  factors  and  the  number  of vehicles  on  SO 2   concentrations. Impinger was used for air sampling, and pararosaniline method was used for determining SO 2  concentration. Sampling and calculation  of the number of passing vehicles were performed 3 times ie in the morning, afternoon and evening. Based on the results of the study, the highest concentrations of SO 2  were on the range of 15-21 mg/Nm3.